Study on the state of knowledge of medical students about the glycemic index of popular food products in Poland. A survey study - Czarnota, Jakub; Dobrzyński, Michał; Skubel, Tomasz; Drozd, Małgorzata; Dudek, Iga; Sokół, Dorota; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Introduction: The glycemic index (GI) is a helpful indicator in composing a healthy diet, especially for people at risk of carbohydrate metabolism disorders. High GI products are quickly digested and absorbed in the human body. There is a sharp increase in postprandial glucose and insulin secretion, followed by a rapid decrease in blood glucose level, which results in increased glucagon secretion and increased appetite. A high GI diet may be one of the causes of insulin resistance and obesity. Aim: The aim of the study is to examine the state of knowledge of medical students studying in Poland about the glycemic index of popular food products. Material and Methods: An anonymous online survey was conducted. The answers of 140 medical students of polish medical universities were analyzed. Results: Despite the fact that 52.1% of respondents declared that they are interested in the subject of healthy eating, milk chocolate and honey were most often recognized as high GI by the respondents (respectively 90.6% and 84,1% of answers). However, these products are classified as low/medium GI products. A baguette with a very high GI obtained 70.3% of responses. Another product with a medium Gi, boiled potatoes, got 56.5% response. Conclusion: The knowledge of medical students about the glycemic index is not large, despite expressed interest in the subject of healthy eating.